Fucoidans from the brown seaweeds Undaria pinnatifida and Fucus vesiculosus as inhibitors of coagulant and phospholipase A2 activities of pit viper Lachesis muta venom and purified enzymes - Camila Castro-Pinheiro; Eladio F. Sanchez; Corinna A. Dwan; Barbara C. Wimmer; Alan T. Critchley; André L. Fuly (Journal of Applied Phycology, 2026)
Snakebite envenomation is a neglected tropical disease and incidents of the pit viper Lachesis muta cause hemorrhage, muscle damage, blood coagulation disturbances, and even death; the proteases and phospholipase A 2 (PLA 2 ) of snake venoms contribute to such toxic effects. This work evaluated the inhibitory effect of commercial fucoidans from two species of brown seaweeds Fucus vesiculosus (FVF) and Undaria pinnatifida (UPF) against the coagulant and PLA 2 activity of Lachesis muta venom and two purified enzymes, a thrombin-like enzyme and PLA 2 , denoted TLE–1 and LM-PLA 2 –I, respectively. Fucus vesiculosus and U. pinnatifida fucoidans were incubated with L. muta venom and enzymes for 5 min at 37 °C, followed by assays, including the plasma and fibrinogen coagulation, hydrolysis of the substrates of proteases (S–2238 and S–2288), and hydrolysis of the substrate of PLA 2 enzymes, NBD-PC. Fucus vesiculosus and U. pinnatifida fucoidans inhibited the plasma coagulation of L. muta venom, but not the coagulation of TLE–1. However, both fucoidans fully prevented the coagulation of fibrinogen caused by L. muta venom and TLE–1. Fucus vesiculosus and U. pinnatifida fucoidans inhibited 60% and 40% hydrolysis of S–2238 of L. muta venom and TLE–1, respectively. Using the substrate S–2288, the fucoidans did not affect the hydrolysis of L. muta venom and inhibited 40% of hydrolysis caused by TLE–1. Fucus vesiculosus and U. pinnatifida fucoidans inhibited 40% and 20% of the PLA 2 activity of L. muta venom and LM-PLA 2 –I, respectively. These two fucoidans should be investigated as complementary or potential adjuvants for SBE inflicted by L. muta venom in more detail.